1997
DOI: 10.1200/jco.1997.15.7.2596
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of continuous infusion carmustine and cisplatin followed by cranial irradiation in adults with newly diagnosed high-grade astrocytoma.

Abstract: This chemotherapy regimen appears to have significant activity and may prolong survival in adults with newly diagnosed high-grade astrocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…Neoadjuvant chemotherapy has the potential to greatly enhance the discovery of truly active agents as well as the early identification of ineffective therapies in a disease where chemotherapy has been only marginally effective. In a phase II setting, Grossman et al administered BCNU and CDDP as a 72-h continuous intravenous infusion prior to radiation therapy (Grossman et al, 1997). Of the 52 patients studied, 42% had a partial response and 53% had stable disease.…”
mentioning
confidence: 99%
“…Neoadjuvant chemotherapy has the potential to greatly enhance the discovery of truly active agents as well as the early identification of ineffective therapies in a disease where chemotherapy has been only marginally effective. In a phase II setting, Grossman et al administered BCNU and CDDP as a 72-h continuous intravenous infusion prior to radiation therapy (Grossman et al, 1997). Of the 52 patients studied, 42% had a partial response and 53% had stable disease.…”
mentioning
confidence: 99%
“…The high risk of myelosuppression by nitrosourea is a well-known problem, and we have previously experienced such high toxicity profiles [5,7,16]. Moreover, many studies have reported that the hematological toxicities induced by nitrosourea are well tolerated by the majority of patients [4][5][6][7]18]. In the past and despite its toxicity, use of this kind of chemotherapeutic agent was justified because it was the only drug for extending survival in this devastating disease.…”
Section: Discussionmentioning
confidence: 99%
“…Synergy in the anticancer effects of nitrosourea and temozolomide has been demonstrated in a phase II trial for recurrent glioblastoma [13]. The idea of combining continuous infusion of a lipophilic drug such as nitrosourea with a hydrophilic agent such as CDDP for treatment of malignant glioma was developed as a potential improved anticancer strategy [4,15]. In Korea and Japan, ACNU rather than BCNU and CCNU has been widely used for high-grade glioma treatment because of its easy availability [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of combining the continuous infusion of a lipid-soluble drug with a water-soluble agent for malignant glioma was developed as a potential strategy [7,10,12,13] . This tactic is based on the observation that even hydrophilic agents can cross the blood-brain barrier (BBB) when a sustained blood level is continuously maintained [14] , and the anticancer effect is even The number of cycles of each treatment are shown in parentheses.…”
Section: Discussionmentioning
confidence: 99%